UJI AKTIVITAS ANTIDIABETES CUKA KULIT NANAS (Ananas comosus L. Merr.) PADA TIKUS PUTIH (Rattus norvegicus) JANTAN GALUR WISTAR YANG DIINDUKSI ALOKSAN - Mohammad Affan Dwica Putra; Siti Nur Jannah; Agung Janika Sitasiwi (Jurnal Pro-Life, 2020)
Diabetes mellitus is a metabolic disorder characterized by increased levels of glucose in the blood (hyperglycemia). The increasing number of diabetics in the world encourages the discovery of certain drugs that are effective and relatively safe for managing diabetes. One alternative medicine that can be used is vinegar. Pineapple skin can be an alternative raw material for making vinegar because it contains a large amount of sugar and contains acetic acid and various secondary metabolites that can reduce blood glucose levels. The purpose of this study was to determine whether pineapple skin vinegar has antidiabetic activity. The test was carried out by dividing each of the 4 rats into six groups namely normal control, positive control, negative control, and three test groups that were given pineapple skin vinegar as much as 0.2, 0.4, and 0.8 cc. The treatment was carried out for 28 days, starting 4 days after induction of an alloxan dose of 150 mg / kg body weight. Measurement of blood glucose and body weight of rats were carried out before induction, after induction, and on the 7th, 14th, 21st, and 28th day, while the measurement of feed consumption was carried out every day starting from the day of pineapple skin vinegar administration. The results of the analysis showed that the administration of pineapple skin vinegar by 0.4 cc with acetic acid levels of 1.43% can reduce blood glucose levels most significantly that is 41.63%.Keywords: vinegar, pineapple skin, acetic acid, antidiabetic